Discitis Following Radiofrequency Nucleoplasty: A Case Report - Shofwan, Said (Anesth Pain Med, 2020)
INTRODUCTION: Radiofrequency nucleoplasty is a minimally invasive procedure to treat chronic low back pain, especially mild degenerative disc diseases. Discitis after radiofrequency nucleoplasty is a rare case. CASE PRESENTATION: A 62-year-old male patient with a chief complaint of 10 years low back pain, gradually worsening for the last two years, a history of hypertension, chronic kidney disease, and routine dialysis twice a week, referred to the center. He underwent a lumbar medial branch block using radiofrequency and radiofrequency nucleoplasty procedure of lumbar 4-5 (L4-L5). Three weeks after the intervention, he could not move his legs, associated with urinary and fecal incontinence. MRI (magnetic resonance imaging) of the lumbar spine was performed, and the results indicated hyperintensity in L4-L5, suspicious of discitis. Laminectomy at L4 and L5 was performed. Eight months after surgery, the patient could feel and lift legs, and urinary and fecal incontinence was also controlled. CONCLUSIONS: Early diagnosis of discitis is critical and challenging. Delay in diagnosis may lead to treatment delay and the development of neurological deficits. Comprehensive treatment with bed rest, antimicrobial therapy, and sensible application of timely surgery are essentials to an optimal outcome.